Three New Cembranoids from the Taiwanese Soft Coral Sarcophyton ehrenbergi - Wang, Shang-Kwei (MDPI, 2012)
In order to search for new bioactive substances from marine organisms, we have investigated the acetone extracts of the soft coral Sarcophyton ehrenbergi collected at San-Hsian-Tai, Taitong County, Taiwan. Chromatographic fractionation of the extracts of the octocoral S. ehrenbergi led to the isolation of three new cembranoids, (+)-12-ethoxycarbonyl-11Z-sarcophine (1), ehrenbergol A and B (2 and 3). The structures of these isolated metabolites were elucidated through extensive spectroscopic analyses. Moreover, metabolites 1–3 were evaluated in vitro for their cytotoxicity towards selected cancer cell lines and antiviral activity against human cytomegalovirus (HCMV).